Growth performance and meat characteristics of feedlot cattle fed R-salbutamol or zilpaterol hydrochloride during the finishing period - Webb, E.C. (Edward Cottington) (University of Pretoria, 2015)
Dissertation MSc(Agric)--University of Pretoria, 2014